Prioritization of Trans-Sumatra Toll Road Segment Phase II Using The Analytical Hierarchy Process - Muhammad Khairi Rifqi; Manahan Parlindungan Saragih Siallagan (Jurnal Impresi Indonesia, 2025)
The construction of the Trans-Sumatra Toll Road (JTTS) is a national strategic project aimed at strengthening regional connectivity and boosting economic growth in Sumatra. PT Hutama Karya (Persero) is tasked with building over 2,700 kilometres of toll roads in Sumatra, as mandated by the Indonesian government. However, the implementation of Phase II has faced challenges such as delays in land acquisition, limited budgets, complex geographical conditions. These issues led to deviations from the planned time and budget, which could hinder the achievement of the project's national goals. This study aims to assist PT Hutama Karya, particularly the Toll Road Planning Division (RJT), in prioritizing toll road segments for Phase II. To address this, study employs the Analytical Hierarchy Process (AHP), a multi-criteria decision-making method. A hierarchical structure based on key objectives, evaluation criteria, and segment alternatives is developed, with expert-based weighting. Interviews with four subject matter experts (SMEs) identified four main criteria: traffic volume, land readiness, investment costs, and geographical conditions. The three segments evaluated were Betung–Tempino–Jambi, Jambi–Rengat, and Rengat–Pekanbaru. The analysis, using a pairwise comparison questionnaire processed with SuperDecision software, revealed that the Betung–Tempino–Jambi segment is the best to prioritize due to its high traffic volume, better land readiness, lower investment costs (Rp21.01 trillion), and more favorable geographical conditions. Rengat–Pekanbaru ranked second, while Jambi–Rengat ranked third due to higher costs and more challenging conditions. This study contributes practical insights for PT Hutama Karya and suggests future research directions in infrastructure management.